Endoscopic-assisted robotic pyelolithotomy: a viable treatment option for complex pediatric nephrolithiasis. Issue 2 (April 2020) - Roth, Joshua D.; Gargollo, Patricio C.; DaJusta, Daniel G.; Lindgren, Bruce W.; Noh, Paul H.; Rensing, Adam J.; Krambeck, Amy E.; Whittam, Benjamin M.; ,
Summary: Introduction and objective: Endourological and percutaneous approaches are the standard of care for treatment of pediatric urolithiasis. However, in certain situations, an endoscopic-assisted robotic pyelolithotomy (EARP) can be an acceptable alternative. Limited data exist on pediatric EARP; thus, the authors describe their experience. Methods: Patient selection: The authors retrospectively analyzed the records of all robotic procedures performed at five institutions from 7/09–10/17 to identify patients who underwent EARP. The authors collected demographics data, indications, operative time, and postoperative complications. Stone composition was reported as the majority composition (≥50%), unless any uric acid or struvite was noted, and those stones were classified as such. Technique: Through a traditional or hidden incision endoscopic surgery (HIdES) robot pyeloplasty approach, the authors are able to easily pass a flexible endoscope through a robotic trocar and into the renal collecting system to perform pyeloscopy or ureteroscopy. Stones were primarily retrieved via the pyelolotomy and, if indicated, treated with laser lithotripsy. Results: The authors identified 26 patients who underwent EARP in 27 renal units. Median patient age was 12.2 years (interquartile range [IQR] 6.1–14.5 years), and body mass index was 17.5 kg/m 2 (IQR 16.5–25.4 kg/m 2 ). The median pre-operative dimension of the largest stone was 9.0 mm (IQR 5.8 mm–15.0 mm). Reasons for EARP: 21 (77.8%) concomitant pyeloplasty, four (14.8%) altered anatomy precluding other techniques, and two (7.4%) multiple large stones. Multiple stones were present in 20 renal units (74.1%). Stones were located in the renal pelvis in nine (33.3%), lower pole in 10 (37.0%), ureter in one (3.7%), and multiple locations in seven (25.9%). Hidden incision endoscopic surgery approach was used in 14 (51.9%), and the median operative time was 237.5 min (IQR 189.8–357.8 min) with a median length of stay 1.0 day (IQR 1.0–2.0 days). Stone composition included calcium oxalate in 14 (51.9%), calcium phosphate in five (18.5%), cysteine in two (7.4%), struvite in two (7.4%), and unknown in four (14.8%). Overall stone free status was 19 (70.4%); of the eight (29.6%) renal units with residual stones, four underwent ureteroscopy, two extracorporeal shockwave lithotripsy (ESWL), one spontaneously passed, and one underwent percutaneous nephrolithotomy (PCNL). After secondary treatment, final stone free rate was 96.3%. Complications included stent migration and admission for urosepsis. At a median follow-up of 12 months (IQR 6.2–19.2 months), five (18.5%) had stone recurrence. Conclusions: Endoscopic-assisted robotic pyelolithotomy is a reasonable treatment option for select pediatric patients with concomitant ureteropelvic junction obstruction and nephrolithiasis or pediatric patients with stones inaccessible by standard methods. Summary Figure Extrarenal view of the operative field from the laparoscopic camera depicting the flexible nephroscope in the renal pelvis performing nephroscopy. Summary Figure